Promise not to tell : a novel - McMahon, Jennifer, 1968- (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2016)
Returning to her small home town in Vermont to care for her Alzheimer's patient mother, reserved forty-one-year-old nurse Kate finds herself inadvertently drawn into the murder investigation of a young girl, a case that reminds her of the death of an impoverished childhood friend years earlier.
Keywords: Nurses -- Fiction; Alzheimer's disease -- Fiction; Ghost stories; Vermont -- Fiction; Mystery fiction; Suspense fiction